The STRong lensing Insights into the Dark Energy Survey (STRIDES) 2016 follow-up campaign – I. Overview and classification of candidates selected by two techniques. Issue 1 (24th August 2018) - Treu, T; Agnello, A; Baumer, M A; Birrer, S; Buckley-Geer, E J; Courbin, F; Kim, Y J; Lin, H; Marshall, P J; Nord, B; Schechter, P L; Sivakumar, P R; et al.
ABSTRACT: The primary goals of the STRong lensing Insights into the Dark Energy Survey (STRIDES) collaboration are to measure the dark energy equation of state parameter and the free streaming length of dark matter. To this aim, STRIDES is discovering strongly lensed quasars in the imaging data of the Dark Energy Survey and following them up to measure time delays, high resolution imaging, and spectroscopy sufficient to construct accurate lens models. In this paper, we first present forecasts for STRIDES. Then, we describe the STRIDES classification scheme, and give an overview of the Fall 2016 follow-up campaign. We continue by detailing the results of two selection methods, the outlier selection technique and a morphological algorithm, and presenting lens models of a system that could possibly be a lensed quasar in an unusual configuration. We conclude with the summary statistics of the Fall 2016 campaign. Including searches presented in companion papers (Anguita et al.; Ostrovski et al.), STRIDES followed up 117 targets identifying 7 new strongly lensed systems, and 7 nearly identical quasars, which could be confirmed as lenses by the detection of the lens galaxy. 76 candidates were rejected and 27 remain otherwise inconclusive, for a success rate in the range of 6–35 per cent. This rate is comparable to that of previous searches like SDSS Quasar Lens Search even though the parent data set of STRIDES is purely photometric and our selection of candidates cannot rely on spectroscopic information.